Contextual Leadership for Model Kindergarten Schools through Human Capital Lens - An Pheakdey Ouch; Sambo Ke; Swe Zin Linn Phyu; Bunhe Harth (Journal of Education Research, 2026)
While the success of model kindergarten schools mainly relies on the principal’s effective leadership, there appear to be limited studies that provide a complete review of effective leadership for model kindergarten schools (MKS). This article aims to synthesize the variety of leadership styles successfully employed in kindergarten schools and analyze how these leadership styles contribute to the effective implementation of the Model Kindergarten School Standard(MKSS). This study adopted a literature review approach and employed document analysis as a research design by reviewing research articles from Google Scholar and different documents, including books and policy documents from the Ministry of Education, Youth, and Sport (MoEYS). The findings show that principals’ particular global and democratic leadership aligned most consistently with the kindergarten goals, all stakeholders, the kindergarten setting, time allocation, resource-limited context, and diverse setting helps all kindergarten schools meet MKSS. Through the Human Capital perspective, MoEYS has to invest in conducting future studies and framing contextual leadership for Model Kindergarten School principals.